LANGUAGE AWARENESS WITHIN THE CONTEXT OF CHANGING PERSPECTIVES ON GRAMMAR PEDAGOGY - Hamed Barjesteh; Reza Vaseghi (University of Muhammadiyah Purwokerto, 2012)
In 1970s, Language Awareness (LA) was put forward, primarily by modern linguists, as a new ‘bridging’ element in the UK school curriculum. It was viewed as a solution to several of the failures in the UK schools: illiteracy in English, failure to learn foreign languages, and divisive prejudices. To Van Lier (2001) current interest in LA stems from three sources: Pedagogically oriented LA, Consciousness raising, and critical perspective. This paper concentrates on psycholinguistic focus on consciousness-raising (hereafter C-R activities) and explicit attention to language form or grammar. Three relevant issues are discussed here. Firstly, the nature of LA, its principles, objectives and procedures are discussed. Secondly, this study delves into the main justifications and implications of LA. Last but not the least, this paper tries to present an overview of the rationale behind the use of C-R activities in teaching grammar and current perspectives in grammar teaching. Key words: Language Awareness, Grammar pedagogy, Consciousness Raising, Critical Perspectives